Pembangunan Moderasi Beragama Berbasis Potensi Kedaerahan pada Provinsi Aceh - Fikri, Hasanul (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2024)
This policy paper explains that Aceh Province has special characteristics compared to other provinces in Indonesia, namely in terms of regional regulation, social life, and culture. However, the existence of these special characteristics has a negative impact on the low KUB index and religious moderation. Thus, an analysis is needed to solve this problem. The analysis method used to solve the problem is qualitative and the data will be analyzed using SWOT as a basis for using potential as a resource in solving the problem. The results of the analysis reveal that: 1) There is no need to make changes to the indicators of the religious harmony index in Aceh Province if the development of religious moderation has been implemented optimally, namely by maximizing the role of actors of religious harmony, budget, and managerial in the development of religious moderation; 2) The development of religious moderation is carried out by using the potential of existing strengths as supporters to create religious harmony in the application of religious moderation. The conclusion is that the development of religious moderation can be carried out by accommodating the special characteristics and characteristics of the region.